2012
DOI: 10.1371/journal.pone.0040930
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Contributed to Modulation of Spinal Nociceptive Information Related to ephrinBs/EphBs

Abstract: There is accumulating evidence to implicate the importance of EphBs receptors and ephrinBs ligands were involved in modulation of spinal nociceptive information. However, the downstream mechanisms that control this process are not well understood. In the present study, we investigated whether phosphatidylinositol 3-kinase (PI3K), as the downstream effectors, participates in modulation of spinal nociceptive information related to ephrinBs/EphBs. Intrathecal injection of ephrinB1-Fc produced a dose- and time-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 55 publications
(100 reference statements)
4
62
2
Order By: Relevance
“…We speculate that species differences may account for these differences as we examined pain behaviors in mice and the previous study used rats. Indeed, in other study, the activation of spinal EphB receptors by using another reagent, ephrinB1-Fc, also produced thermal hyperalgesia and mechanical allodynia in mice (Ruan et al, 2010;Yu et al, 2012). Nevertheless, other factors, such as the use of different doses and different nociception tests, also potentially contributed to the discrepancies between our results and those of the previous study.…”
Section: Ephrinb-ephb Signaling and Paincontrasting
confidence: 81%
“…We speculate that species differences may account for these differences as we examined pain behaviors in mice and the previous study used rats. Indeed, in other study, the activation of spinal EphB receptors by using another reagent, ephrinB1-Fc, also produced thermal hyperalgesia and mechanical allodynia in mice (Ruan et al, 2010;Yu et al, 2012). Nevertheless, other factors, such as the use of different doses and different nociception tests, also potentially contributed to the discrepancies between our results and those of the previous study.…”
Section: Ephrinb-ephb Signaling and Paincontrasting
confidence: 81%
“…These findings demonstrate that ephrinB/EphB signalling is a key regulator of physiological and pathological processes underlying pain, suggesting that it may act as a new molecular target for pain prevention and relief. Indeed, in other study, activation of spinal EphB receptors using another reagent, eph-rinB1-Fc, also produced thermal hyperalgesia and mechanical allodynia in mice (Ruan et al, 2010;Yu et al, 2012). Spinal application of ephrinB2-Fc, which can activate EphB receptors, caused thermal hyperalgesia and mechanical allodynia.…”
Section: Ephrinb/ephb Signalling and Painmentioning
confidence: 82%
“…The induction and maintenance of central sensitization are dependent on maladaptive alterations in the expression, distribution, and activity of ion channels, receptors and intracellular signal transduction pathways. For instance, ephrinB/EphB signalling can modulate spinal nociceptive processing through MAPKs-and PI3K-dependent mechanisms (Ruan et al, 2010;Yu et al, 2012). Exogenous ephrinB-Fc or increased expression of ephrinB proteins induced by tissue injury or inflammation directly activates EphB receptors in nociceptors or sensory neurons.…”
Section: Ephrinb/ephb Signalling and Central Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our and other studies also demonstrated that activation of spinal ephrinBs/EphBs system played a critical role in the development and maintenance of chronic pain after peripheral nerve injury (18)(19)(20)(21)(22). There are striking similarities between neuropathic pain and opiate dependence and tolerance, and neuropathic pain and opiate dependence may share some common mechanisms (23,24).…”
mentioning
confidence: 74%